Crescimento e produção de pimentão, tipo páprica, sob diferentes níveis de adubação de nitrogênio e fósforo - Alves, Leonardo Porpino (Universidade Federal Rural do Semi-Árido, 2006)
Objecting to evaluate the productive aspects of the culture of the Bell pepper, paprika type, submeitted to different levels of phosphorus and nitrogen, an experiment was carried out at Bahama Agroindustrial farm, located in the town of Parazinho-RN, where there is a kind of soil classified as Alfisol. The treatment consisted of 5 different doses of nitrogen and phosphorus: 0, 85, 100, 115, and 130% of the conventional proportion used at the farm, being the phosphorus different just in the sowing. The delineating experiment was conducted in blocks completely randomized with portions of three double rows with 1,5m between rows,0,30m between double rows and 0,25m among plants with the length of 25m, adding up to 48plants per row (on average), the used variety was the Ver one. In 64, 86, 126, 147 and 163 days after the sowing, two plants of medium size per portion for each time were picked off from the lateral rows, and for the production analysis, just the fruits picked off in the latest hearvest were considered as commercial fruits. Within the factors studied, it was observed that the dose of nitrogen applied through fertirrigation that stood out mostly among the treatments, not concerning the variable studied, was the standard one, with 295 kg.ha-1 used at the farm, it was also found that the phosphorus when applied in the sowing, the largest applied dose P4 (144 kg.ha-1), got the best results in the fruit dry matter, besides the total productivity, the N2P4 treatment, the farm s conventional dose of nitrogen (295 kg.ha-1 of N), combined with the highest dose of phosphorus (144 kg.ha-1 de P), obtained values of gross income, net income, rates of return, and index of profitability, representing that way, the best cost of benefit for the producer
Growth and production of bell pepper, type paprika, under different levels of manuring of nitrogen and phosphorus
Keywords: Pimentão; Páprica; Fertirrigação; Produção; Bell peper; Paprika; Fertirrigation and Production; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA